Secret of the stones - Bradman, Tony 1954- (Barrington Stoke, 2017)
Maglos is the only son of the High Priest of Stonehenge. His destiny is to wear the crown of his people, to lead their sacrifices to the ancient Gods of light and darkness. But as the sun rises on a midsummer day in 2300 BC, a terrible act of betrayal casts Maglos away from his home. His only allies are two strange men from distant lands, men who carry with them the secret of the stones
Keywords: Bronze age / Juvenile fiction; Stonehenge (England) / Juvenile fiction; Bronze age; England / Stonehenge; Historical fiction; Fiction; Juvenile works